Selection and metabolic characterization of mesophylic starter cultures for optimizing the sensory attributes of fruit flavoured Maas - Arendse, Garron Mark (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2000.